2020
DOI: 10.1002/asia.201901802
|View full text |Cite
|
Sign up to set email alerts
|

2020 Roadmap on Carbon Materials for Energy Storage and Conversion

Abstract: Carbon is a simple, stable and popular element with many allotropes. The carbon family members include carbon dots, carbon nanotubes, carbon fibers, graphene, graphite, graphdiyne and hard carbon, etc. They can be divided into different dimensions, and their structures can be open and porous. Moreover, it is very interesting to dope them with other elements (metal or non‐metal) or hybridize them with other materials to form composites. The elemental and structural characteristics offer us to explore their appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 170 publications
(80 citation statements)
references
References 92 publications
0
72
0
Order By: Relevance
“…However, its low theoretical capacity of 372 mAh g À 1 and poor rate capability severely limit its application in high-demand energy storage systems such as electric vehicles and stationary energy storage grids. [35,36] FGnPs have displayed outstanding lithium storage properties and stability, due to their large specific surface area, highquality graphitic basal plane and edge-protection provided by the most stable CÀ F bonds, making them a promising anode material. [20] However, using dangerous F 2 gas limits the practical uses of FGnPs.…”
Section: Resultsmentioning
confidence: 99%
“…However, its low theoretical capacity of 372 mAh g À 1 and poor rate capability severely limit its application in high-demand energy storage systems such as electric vehicles and stationary energy storage grids. [35,36] FGnPs have displayed outstanding lithium storage properties and stability, due to their large specific surface area, highquality graphitic basal plane and edge-protection provided by the most stable CÀ F bonds, making them a promising anode material. [20] However, using dangerous F 2 gas limits the practical uses of FGnPs.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, with the rapid evolution of wind energy, solar energy, electric vehicle and smart grid, the exploitation of large-scale energy storage devices has been a crucial issue. [34,35] Rechargeable AZIBs have emerged and exhibited a promising application due to compelling advantages, such as the low-toxicity and high abundance of zinc in the earth's crust (79 ppm), the suitable redox potential of zinc (À 0.763 V vs SHE), the large specific gravimetric capacity (820 mAh g À 1 ), as well as the higher ionic conductivity (1 S cm À 1 ) and safety of aqueous electrolytes. [36,37] At present, AZIBs are regarded as one of the preferred high-performance candidates for large-scale energy storage, and thus trigger the strong and extensive research.…”
Section: Statusmentioning
confidence: 99%
“…Importantly, nonmetal doping plays an important role in arousing catalytic activity of inert basal plane of graphene by destroying sp 2 hybridization and inducing charge redistribution. [34] Jiao et al [33] demonstrated that the hybridization energy level of hydrogen adsorbate and active sites may split into bonding state and anti-bonding state, which was responsible for the hydrogen adsorption strength tuned by dopants, causing different hydrogen binding energy with various configurations of doped graphene (Figure 4a). Among them, B, N and P could select as preferential alternatives to achieve excellent HER properties with low uphill energy barriers (Figure 4c).…”
Section: Heteroatom Dopingmentioning
confidence: 99%